DEVELOPMENT OF CULTURE INNOVATION CAPABILITY OF BALI GOVERNMENT TO WELCOME GLOBAL MARKETS OF TOURISM - Gede Wirata; Ida Ayu Putu Sri Widnyani (Universitas Pendidikan Ganesha, 2017)
The forces of globalization have been able to shift patterns and lifestyle of people of the world, no exception in the tourism industry. The process of globalization has changed the form and structure of the tourism industry. The phenomenon requires countries in the world to evolve in a new system of government which is adaptive, innovative and sensitive to changes. Bureaucratic reform in Indonesian has been proceeding for many years. However, persisting problems concerning bureaucracy have yet to be resolved. This snag may arise due to the lack of the creativity and innovation culture within government bureaucracy. Therefore, bureaucratic reform should be directed more to innovation culture and programs including tourism sector in order to enhance the bureaucracy’s innovation capability.